A Survey on Prevalence of Ocular Complications and It's Risk Factors in Diabetic Patients Referred to Diabetic Center of Nader Kazemi Clinic Shiraz- Iran 1998-2010 - ali khani jeihooni; mansour kashfi; mohammad mehdi hazavehei (Fasa University of Medical Sciences, 2013)
Background & Objective: With respect to increasing prevalence of diabetes, the chance for incidence of ocular complications among diabetics, this study was conducted to investigate the prevalence and risk factors for the incidence of the ocular complications in the patients referred to the Nader Kazemi Shiraz Diabetic center from 1998 to 2010.Materials & Methods: In a cross sectional study , subjects were selected based on a systematic random sampling to investigate the incidence of the ocular complications and factors influencing like wise age, sex, type of diabet, job, education, blood triglyceride (TG) and cholesterol level, Family history of diabetes, history of hypertension, history of participation in educational classes, method of treatment, duration of diabetes and fasting blood sugar were considered.Results: Ocular complications were found among 229 diabetic patients (32.6%). Ocular complications of type II diabetic patients than in patients with type I diabetes (P<0. 005). Factors such as job(P=0. 022), history of participation in educational classes(P<0. 001), education(P<0. 001), Family history of diabetes(P<0. 001), blood triglyceride (TG) (P=0. 021), duration of diabetes(P<0. 001),age (P<0. 001), method of treatment(P<0. 001)and fasting blood sugar (P<0. 001) had a significant relationship with the occurrence of ocular complication. But other risk factors such as hypertension, gender and cholesterol levels were not statistically significant relationship with the occurrence of ocular complication.Conclusion: Given the prevalence of ocular complications, continuing education on the disease of diabetes complications, it can have a role in reducing the occurrence of ocular complications.